Globalization & crime - Aas, Katja Franko (London SAGE, 2013)
Globalization & Crime brings together the closely related subjects of criminology and global sociology. Ideal for upper-level undergraduate and postgraduate students, it examines established topics such as human trafficking and smuggling, migration and organized crime. It also delves into new territory and explores the issues surrounding international criminal justice, comparative criminology, green criminology and human rights. New to this Second Edition is a chapter dedicated to the impact that the war on terror has had on the rule of law and a detailed discussion on the growing topic of cosmopolitan criminology. Complete with extensive references, helpful suggestions for further reading and a detailed glossary, this book will prove essential reading for students and academics in criminology, globalization, sociology and other social sciences.
1. Crime, fear and social exclusion in the global village -- 2. Global mobility and human traffic -- 3. Urban criminology and the global city -- 4. The deviant immigrant': migration and discourse about crime -- 5. Global security and the war on terror' -- 6. Governing global risks -- 7. Beyond the state: globalization and state sovereignty -- 8. Controlling cyberspace? -- 9. Criminology between the national, local and global -- 10. Towards a cosmopolitan criminology.
1st ed.: 2007.
Bibliographyand index.
Keywords: Crime and globalization